Frontmatter - Barták, Roman; Ruml, Wheeler; Salzman, Oren (Proceedings of the International Symposium on Combinatorial Search, 2023)
The Sixteenth International Symposium on Combinatorial Search (SoCS) was held at the Aquapalace Hotel Prague, Czech Republic, at July 14–16, 2023, just after the International Conference on Automated Planning and Scheduling (ICAPS). The symposium co-chairs were Roman Barták, Wheeler Ruml, and Oren Salzman.